Determinants of customer experience for luxury hotels in Malaysia - Raini Anne Laipan; Mazalan Mifli; Oscar Dousin; Bamini KPD Balakrishnan (Human Resource Management Academic Research Society, 2022)
To meet the needs of an increasing number of people who want to take advantage of technology, the lodging industry has begun to offer a diverse range of customer experiences. Scholars have paid more attention to how customers feel about their hotel stays, which is not new. Through a PLS-SEM analysis, this paper shows the results of a survey that asked customers of four- and five-star hotels how they felt about the actions hotels took to improve their service quality. The study gives practitioner information about the most of factor service quality to influence the customer experience. The main goals are to find out the "service quality hotel" quality (Interaction quality, physical environment quality and outcome quality) practises and to see if there is a link on how customers feel about their stay. The results of this study supported the research hypotheses. Study showed that customers experience is most effected by the quality of interactions, followed by the physical environment’s quality, and outcomes quality at hotels, which provides them a significant experience of hedonic, economic, social and altruistic values. Implications, limitations, and possible directions for future research are also given.